IL‐10 prevents aging‐associated inflammation and insulin resistance in skeletal muscle. Issue 2 (3rd November 2016) - Dagdeviren, Sezin; Young Jung, Dae; Friedline, Randall H.; Noh, Hye Lim; Kim, Jong Hun; Patel, Payal R.; Tsitsilianos, Nicholas; Inashima, Kunikazu; Tran, Duy A.; Hu, Xiaodi; Loubato, Marilia M.; Craige, Siobhan M.; et al.
ABSTRACT: Altered energy balance and insulin resistance are important characteristics of aging. Skeletal muscle is a major site of glucose disposal, and the role of aging‐associated inflammation in skeletal muscle insulin resistance remains unclear. To investigate, we examined glucose metabolism in 18‐mo‐old transgenic mice with muscle‐specific overexpression of IL‐10 (M IL10 ) and in wild‐type mice during hyperinsulinemic‐euglycemic clamping. Despite similar fat mass and energy balance, M IL10 mice were protected from aging‐associated insulin resistance with significant increases in glucose infusion rates, whole‐body glucose turnover, and skeletal muscle glucose uptake (~60%; P <0.05), as compared to age‐matched WT mice. This protective effect was associated with decreased muscle inflammation, but no changes in adipose tissue inflammation in aging M IL10 mice. These results demonstrate the importance of skeletal muscle inflammation in aging‐mediated insulin resistance, and our findings further implicate a potential therapeutic role of anti‐inflammatory cytokine in the treatment of aging‐mediated insulin resistance.—Dagdeviren, S., Jung, D. Y., Friedline, R. H., Noh, H. L., Kim, J. H., Patel, P. R., Tsitsilianos, N., Inashima, K., Tran, D. A., Hu, X., Loubato, M. M., Craige, S. M., Kwon, J. Y., Lee, K. W., Kim, J. K. IL‐10 prevents aging‐associated inflammation and insulin resistance in skeletal muscle. FASEB J. 31, 701–710 (2017). http://www.fasebj.org